The Concept of Multicultural Approach through IPS Education and Its Relevance in the 21st Century Era - Silvi Tabah Hati (Universitas Muhammadiyah Enrekang, 2022)
Abstract The factual condition illustrates that the condition of the Indonesian people is increasingly critical. This incident was triggered by various unresolved social problems. Social problems are a scourge of shared homework, especially teachers and the community. A multicultural approach integrated with Social Sciences (IPS). Educational learning offers an alternative through the application of diversity-based educational strategies and concepts in the Community. This paper aims to describe theoretically how to integrate multicultural approaches and social studies. So, the portion of multicultural education and social studies is able to equip students with sensitivity in dealing with social symptoms and problems that are rooted in differences. These differences such as ethnicity, race, religion, and values ​​that occur in the community environment for the cultivation of unity. Therefore, this substance and learning model will be able to focus learning on appreciating cultural diversity in the 21st century era. Keywords: Social Problems, Multicultural Approach, Social Science Education. THE CONCEPT OF A MULTICULTURAL APPROACH THROUGH SOCIAL STUDIES EDUCATION AND ITS RELEVANCE IN THE 21ST CENTURY ERA Abstract Factual conditions illustrate the increasingly critical condition of Indonesian society. This incident was triggered by various unresolved social problems. Social problems become the scourge of shared homework, especially teachers and communities. A multicultural approach integrated with Social Sciences (IPS). Educational learning offers an alternative through the application of diversity-based educational strategies and concepts that exist in the Community. This paper aims to theoretically describe how to integrate multicultural and social studies approaches. So, the portion of multicultural education and social studies is able to equip students with sensitivity in dealing with symptoms and social problems that are rooted in differences. These differences include ethnicity, race, religion, and values that occur in the community for the cultivation of unity. Therefore, the substance and model of this learning will be able to focus learning on the passion for cultural diversity in the era of the 21st Century. Keywords: Social Problems, Multicultural Approach, Social Science Education